The influence of pulse current on drop transfer during double-electrode gas surfacing - Sergey K. Elsukov; Ilya V. Zorin; Dmitry S. Nesin (Frontier Materials & Technologies, 2025)
The application of a circuit with a common pulse current source for surfacing with two electrode wires increases the energy efficiency of the arc process and the welding arc technological properties, but requires a more detailed study of the influence of the mode parameters on its stability. In this regard, this paper focuses on studying the dynamics of formation and transfer of metal drops under various modes of pulsed power supply of the welding arc. Using high-speed video filming of the welding arc and synchronized recording of current and voltage signals, a mode was set (average current value was 250 A, maximum current value in pulse was 600 A, arc voltage was ~30 V), which ensured a stable process of transfer of electrode metal by a drop common to two wires without short circuits. It was found that the common drop under the action of electrodynamic forces acquires centripetal acceleration, which contributes to its directed transfer to the weld pool and allows minimizing the amount of spatter on the surface of the base metal. Using mathematical modeling, the nature of the interaction of welding arcs on two wires was confirmed and it was found that even at the stage of the current pulse “hot” phase (600 A, t=0.8 s), the arc pressure on the plate surface is less than when welding with one wire at direct current. The identified effect is associated with a change in the direction of the plasma flow to perpendicular to the wire axis due to an increase in the electrodynamic attractive force of the magnetic fields around the two wire conductors. Together with a decrease in the arc temperature and pressure on the plate surface during the “heat input control” phase of the current pulse (180 A, t=1.4 s), this should help to reduce the heat input and the depth of penetration of the base metal, and, consequently, reduce the degree of dilution of the deposited alloy by the substrate metal. The latter is especially relevant when solving problems of creating a technology for surfacing of relatively thin layers of corrosion-resistant alloys, in particular, on the surface of petrochemical equipment products.